Promoting crystalline grain growth and healing pinholes by water vapor modulated post-annealing for enhancing the efficiency of planar perovskite solar cells. Issue 35 (12th August 2016) - Ge, Qian-Qing; Ding, Jie; Liu, Jie; Ma, Jing-Yuan; Chen, Yao-Xuan; Gao, Xiao-Xin; Wan, Li-Jun; Hu, Jin-Song
Abstract : Water vapor modulated post-annealing is a reproducible and easily-scalable method to promote the grain growth and heal the pinholes for efficient PSCs. Abstract : Mixed organic–inorganic halide perovskite materials have been successfully used as light harvesters in efficient solar cells. Developing reproducible and manageable processes to prepare large-scale highly-crystalline perovskite films with large grains for reducing charge recombination at grain boundaries and thus enhancing the efficiency of large-area perovskite solar cells will advance their practical application. Here we report a reproducible and easily-scalable method using solvent-extraction and water vapor modulated post-annealing to promote the grain growth and simultaneously heal the pinholes in perovskite thin films. Significant enhancement in crystalline grain size and elimination of pinholes are achieved by introducing water vapor in the post-annealing atmosphere. The grain size and morphology are closely related to the amount of water vapor. 2 vol% water in the DMF modulated annealing atmosphere can effectively facilitate the integration of small primary perovskite grains and the merging of grain boundaries as well as the healing of the pinholes during post-annealing, leading to high-quality pinhole-free perovskite films with large-aspect-ratio crystalline grains. As a result, PSCs with a device efficiency of over 17%, corresponding to 14.4% improvement of average efficiency over the devices post-annealed in DMF only atmosphere with the absence of water vapor, and better stability and reduced hysteresis can be readily achieved. Compared with the prevailing anti-solvent dripping method which need precise control of the dripping timing, the present method combining solvent-extraction and water vapor modulated post-annealing is more compatible and reproducible for preparing large-area high-quality perovskite thin films, opening up opportunities for the development of large-area high-performance perovskite solar cells and other optoelectronic devices.